Understanding the mandatory reporting of child sexual abuse in selected special schools, Eastern Cape, South Africa - Nokwenzeka Boyana; Mathabo Khau (Cogent Social Sciences)
Although sexual violence against children is a global problem, it is more pervasive in some regions than others. South Africa is one such context where there is a close connection between the social environment and child sexual abuse (CSA). Despite the government’s efforts mandating the reporting of CSA, its prevalence remains high and has become a significant health and societal issue. In this article, I explore how school management teams (SMT) and school-based support teams (SBST) in designated special schools in the Eastern Cape, South Africa understand the protocols and procedures for reporting CSA. The qualitative study upon which this article is based utilised the interpretive paradigm and phenomenological research design with eleven SMT and SBST members from four purposively chosen special schools. Data was generated using focus group discussions and memory accounts, and Bronfenbrenner’s ecological systems theory (EST) was used to make meaning of the data. The study identifies participants’ lack of knowledge of the existence of the protocols and procedures for reporting CSA. Based on the findings, it is recommended that the South African Department of Education and teacher training institutions facilitate discussions amongst the various departments to promote collaborative efforts in addressing CSA.